Developing Sustainable Supply Chains to Drive Value, Volume II : Management Issues, Insights, Concepts, and Tools-Implementation. - Sroufe, Robert P. (Business Expert Press, 2017)
As we enter the 21st century, we find ourselves faced with two major developments. The first is the emergence of the supply chain as a strategic and tactical weapon. With the emergence of the supply chain, the unit of competition has shifted from the firm to the supply chain. However, with the advent of the supply chain, it is important to recognize that we have to view strategic objectives within a context that stresses not simply the internal operations of the firm but also the elements and stakeholders of the supply chain--elements that include the supplier base, customers, logistics linkages, relationships, transparency, and visibility. We realize that the supply chain is no stronger than its weakest link. The second development is that of sustainability. This paradigm shift is more than simply being environmentally responsible. Rather, it is overall sustainability as measured in terms of the firm's ability to reduce waste, improve profitability, generate strategic competitive advantages, recognize emerging social issues while ensuring that it is safe and treats its employees well. In the past, sustainability was viewed as a marketing fad; this is no longer the case. Sustainability is increasingly becoming at a minimum an expectation and a requirement for doing business (i.e., an order qualifier) and under many conditions something that differentiates firms and makes them more attractive to potential customers (i.e., an order winner).